2005
DOI: 10.1038/sj.bjc.6602697
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of weekly oxaliplatin plus infusional fluorouracil and folinic acid (FUFOX regimen) as first-line treatment in metastatic gastric cancer

Abstract: Oxaliplatin plus fluorouracil/folinic acid (5-FU/FA) every 2 weeks has shown promising activity in advanced gastric cancer. This study assessed the efficacy and safety of weekly oxaliplatin plus 5-FU/FA (FUFOX regimen) in the metastatic setting. Patients with previously untreated metastatic gastric cancer received oxaliplatin (50 mg m À2 ) plus FA (500 mg m À2 , 2-h infusion) followed by 5-FU (2000 mg m À2 , 24-h infusion) given on days 1, 8, 15 and 22 of a 5-week cycle. The primary end point of this multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 23 publications
5
47
0
Order By: Relevance
“…Although the detailed mechanism for oxaliplatin-induced TS gene downregulation needs to be further elucidated, our result is concordant with two previous reports (Raymond et al, 2002;Yeh et al, 2004), which indicated that oxaliplatin could downregulate TS in cancer cells and thus potentiate the efficacy of 5-FU. As oxaliplatin and 5-FU have been shown to be highly synergistic not only in preclinical models (Raymond et al, 1997) but also in subsequent clinical trials (Rothenberg et al, 2003;Chao et al, 2004;Lordick et al, 2005;Schippinger et al, 2005;Cavanna et al, 2006), our data provide important information regarding why the combination of oxaliplatin and 5-FU results in better objective response than single use alone.…”
Section: Discussionmentioning
confidence: 74%
“…Although the detailed mechanism for oxaliplatin-induced TS gene downregulation needs to be further elucidated, our result is concordant with two previous reports (Raymond et al, 2002;Yeh et al, 2004), which indicated that oxaliplatin could downregulate TS in cancer cells and thus potentiate the efficacy of 5-FU. As oxaliplatin and 5-FU have been shown to be highly synergistic not only in preclinical models (Raymond et al, 1997) but also in subsequent clinical trials (Rothenberg et al, 2003;Chao et al, 2004;Lordick et al, 2005;Schippinger et al, 2005;Cavanna et al, 2006), our data provide important information regarding why the combination of oxaliplatin and 5-FU results in better objective response than single use alone.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, oxaliplatin, which had improved the efficacy of 5-fluorouracil (5-FU) treatment in colorectal cancer, was extensively studied in GC. Following promising phase II study results [22][23][24], oxaliplatin was compared with cisplatin in two randomized controlled trials. Both studies were designed to prove the non-inferiority of oxaliplatin compared with cisplatin.…”
Section: Methodsmentioning
confidence: 99%
“…In 2005, there were approximately 400 000 new cases and 300 000 deaths from gastric cancer (Yang, 2006). There is currently no established standard regimen for advanced gastric cancer; however, biweekly oxaliplatin plus 5-fluorouracil (5-FU) and folinic acid (FOLFOX) was well tolerated and yielded median survival times of 9.6 -11.4 months in five phase II studies (Louvet et al, 2002;Al-Batran et al, 2004;Chao et al, 2004;De Vita et al, 2005;Lordick et al, 2005). Considerable published evidence suggests that interindividual variation in response to 5-FU results from variations in the thymidylate synthase (TS) mRNA expression levels of the tumour (Longley et al, 2003).…”
mentioning
confidence: 99%